Web application: efficient immunization by vaccination for children and adults - Jimmy Cruz Fernandez; Laberiano Andrade-Arenas (Institute of Advanced Engineering and Science, 2023)
The investigation analysed the correct use of the vaccination scheme in order to achieve efficient immunization for children and adults in the midst of the pandemic; through the use of a web application that will greatly facilitate people in their immunization, since the web application will allow them to create alerts to have reminders at times personalized by the user. Also, the web application will provide a schedule complete personalized immunization according to the personal information of the registered user, on the other hand they will also be able to view the information of the different vaccination centers to achieve a correct immunization. The methodology was Scrum, allows prepared for change and to be able to adapt, as well as allowing proper planning for efficient work. The result obtained from the investigation can be seen in the sur-vey carried out on parents; where satisfactory percentages were obtained since 98% of respondents indicated that the use of a web application for the correct immunization of people is of the utmost importance, in addition to the survey they were shown the prototype of the application and indicated that its use was efficient, educational and easy to use for everyone.